Post-communist regime change [ a comparative study - Moller, Jorgen , 1979- (Routledge research in comparative politics, 2009)
This book seeks to explain the advent of this post-communist tripartition and elucidate and explain the political pathways of 24 post-communist countries in the period 1990-2005